Chemical Defects and Impurities Introduce Charge Traps to Silicone Rubber: a Quantum Chemistry Study. Issue 1 (1st December 2022) - Duan, Wei; Guo, Guangzhi; Zhu, Guozhu; Zhao, Xuefeng; Pu, Lu; Ju, Zeli; Sun, Haofei; Gao, Jian
Abstract: The distributions of charge trap energy levels in polymer insulation material have an important influence on the charge transport characteristics and breakdown field strength of the polymer insulation, which thus has attracted considerable attention. Based on the quantum chemistry calculations, the characteristics of charge traps induced by different chemical defects and additives in silicone rubber materials are investigated. The projected density of states, and frontier molecular orbital distribution of defective silicone rubber and additive molecules are analyzed. The carbonyl defect, carboxyl defect and diethyl maleate additive all introduce deep electron traps (more than 1eV) in PDMS materials. The carbonyl defect and KH550 additive introduce shallow hole traps (less than 1eV) in PDMS materials. If chemical defects have a dominant contribution to the frontier molecular orbital of polymer is the key factor of whether they can introduce charge traps.